Evaluating Core Clerkships: Lessons Learned From Implementing a Student-Driven Feedback System for Clinical Curricula. (February 2021) - Russel, Sarah M.; Geraghty, Joseph R.; Kobayashi, Kenji R.; Patel, Savan; Stringham, Richard; Hyderi, Abbas; Curry, Raymond H.
Abstract : Problem: Medical schools have implemented various ways to engage students in improving medical curricula. These systems, however, usually focus on the preclerkship curriculum, perhaps because medical students move through this phase of medical education synchronously, making it easier to collect student input. In contrast, clerkship and postclerkship curricula often lack similar levels of student engagement in program evaluation. Approach: To increase communication among students, faculty, and administration during the clinical years of medical education, the Student Curricular Board (SCB) at the University of Illinois College of Medicine's Chicago campus (UICOM–Chicago) developed a student-driven feedback model in 2016 that aimed to parallel the system previously implemented in the preclerkship years. Interested fourth-year students were selected by their peers to represent individual core clerkships, and they communicated regularly with clerkship directors about concerns from current clerkship students. Third-year students applied and were selected to represent their cohort of peers moving through clerkship tracks. Proposed changes and improvements were tracked via novel, student-driven SOAP-Education (SOAP-Ed) progress notes written throughout the academic year. Outcomes: In response to a program evaluation survey conducted after implementation of this pilot, third-year students said they felt that their feedback was taken seriously by faculty and administration. Furthermore, student feedback led to meaningful changes in core clerkship curricula and in the system used to gather clerkship feedback. Clerkship directors expressed appreciation for this partnership, and students said they gained valuable leadership experience and knowledge of curricular development. Next Steps: Current SCB members and curricular leadership plan to assess student and faculty perceptions of this system and its efficacy and work toward expansion to all UICOM campuses. Lessons learned from this student-driven model of feedback in third-year core clerkships will likely add to the conversation on how to better engage medical students as active stakeholders in their own education. Abstract : Supplemental Digital Content is available in the text.